Correlation study of the strain and vibration signals of a beam - Hamizatun, Mohd Fazi (2013)
This work presents the correlation of study of the strain and vibration signal of a beam. This can be achieved by using the forced vibration experiment of a beam which conducted simultaneously with the used of strain gauge on the beam. The focus for this research is on the application of the beam which is commonly used in industry. From the other researcher, the correlation study of the strain and vibration signal is made using Hybrid Kurtosis method which focused on a coil spring differ from this research which be done using a beam.This work involved few steps, firstly, collecting data from the force vibration experimental method, followed by the statistical analysis using Matrix Laboratory (Matlab), Fast Fourier Transform (FFT) and lastly application of Marc Patran software. The experiment performed by considering different frequencies from 10 Hz to 60 Hz. For the statistical analysis, the parameter that used in this analysis are the mean, root mean square (r.m.s), standard deviation, variance, skewness and the kurtosis. By using the analysis, the correlation can be made by the time series data and frequency data. Marc Patran is used to find the analysis on the strain and the displacement of the beam. Displacement used as parameter of the vibration signal. As a result, it was found that the strain signal was linearly proportional to the vibration signals.